Endoscopic third ventriculostomy in hydrocephalus secondary to vestibular schwannomas - Ernesto Enrique Horta-Tamayo; Diana Rosa Ortega-Raez; Luis Cesar Acosta-GonzÃ¡lez; Orestes LÃ³pez-Piloto; Lismary MartÃnez-ValdÃ©s; Martha SuÃ¡rez-Cruz (Revista Cubana de Medicina Militar)
Introduction: Treatment options for hydrocephalus related to posterior fossa tumors have been extensively studied in the pediatric population, but the value of endoscopic third ventriculostomy in hydrocephalus secondary to vestibular schwannoma in adults, is controversial. A systematic search of the medical literature was carried out in Pubmed/Medline and SciElo for the identification and inclusion of articles, in addition to the preprint servers bioRxiv and medRxiv. The following descriptors were used: "Hydrocephalus" and "vestibular schwannomas" or "acoustic neuromas" or "acoustic neurinomas" and "endoscopic third ventriculostomy". The initial search found 195 articles. After selection, 5 articles were chosen for the study. Objective: To specify the role of the endoscopic third ventriculostomy in hydrocephalus secondary to vestibular schwannomas. Development: The articles included a total of 82 patients, in which an improvement of the symptoms was achieved in 86.6% of the cases. The decrease in ventricular diameter was reported in 82.9% of the cases and was only found explicit in 3 articles. Although the failure criteria used were varied, 2 of them predominated: The persistence of progressive symptomatic hydrocephalus and/or the need for shunt placement. Endoscopic third ventriculostomy failure only represented 14.6%. Conclusions: Third ventriculostomy is an acceptable technique with relative success for the treatment of symptomatic obstructive hydrocephalus secondary to vestibular schwannomas.